2018
DOI: 10.1007/s00421-018-3910-3
|View full text |Cite
|
Sign up to set email alerts
|

Change in VO2max and time trial performance in response to high-intensity interval training prescribed using ventilatory threshold

Abstract: A greater volume of HIIT may be needed to maximize the training response for all individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 51 publications
2
28
0
2
Order By: Relevance
“…; Montero and Lundby ; Astorino TA et al. ), threshold‐based dichotomous classification approaches misclassify individuals who have a high probability of a positive response as non‐responders, and 2) using response CIs with zero‐ and/or SWC‐based thresholds provides more information than dichotomous classification approaches regarding an individual's response. Application of these statistical approaches has the potential to improve evidence‐informed exercise prescription decision‐making.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…; Montero and Lundby ; Astorino TA et al. ), threshold‐based dichotomous classification approaches misclassify individuals who have a high probability of a positive response as non‐responders, and 2) using response CIs with zero‐ and/or SWC‐based thresholds provides more information than dichotomous classification approaches regarding an individual's response. Application of these statistical approaches has the potential to improve evidence‐informed exercise prescription decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated how recently proposed statistical approaches (Hopkins 2000b;Swinton et al 2018) can be used to improve the confidence when classifying non-responders. The major novel findings are: 1) despite its growing popularity in the individual response literature (Scharhag-Rosenberger et al 2012;Astorino and Schubert 2014;Ross et al 2015;Gurd et al 2016;Alvarez et al 2017;de Lannoy et al 2017;Montero and Lundby 2017;Astorino TA et al 2018), threshold-based dichotomous classification approaches misclassify individuals who have a high probability of a positive response as non-responders, and 2) using response CIs with zeroand/or SWC-based thresholds provides more information than dichotomous classification approaches regarding an individual's response. Application of these statistical approaches has the potential to improve evidenceinformed exercise prescription decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations